Analysis Employee Engagement and Employee Performance Startup Business: Assessment, Psychological Structure, Discipline (Study Literature Review): Human Resource Management - Jatmiko Murdiono; Josua Panatap Soehaditama; Aswanti Setyawati; Novembriani Irenita; Siti Annisa Wahdiniawati (Dinasti Publisher, 2024)
Abstract: The article analyzing employee engagement and employee performance in startup businesses: assessment of psychological structure and discipline is a scientific literature review article within the scope of human resource management science. The purpose of this writing is to build a hypothesis of the influence between variables which can later be used for further research within the scope of human resource management. The research method used is descriptive qualitative. Data was obtained from previous research that is relevant to this research and sourced from academic online media such as Publish or Perish, Google Scholar, digital reference books and Sinta journals. The results of this article are: 1) Assessment of employee engagement influences in startup businesses; 2) Psychological structure influences employee engagement in startup businesses; 3) Discipline influences employee engagement in startup businesses; 4) Assessment of employee performance influences in startup businesses; 5) Psychological structure influences employee performance in startup businesses; 6) Discipline influences employee performance in startup businesses; and 7) Employee engagement influences employee performance in startup businesses. Keywords: Employee Performance, Employee Engagement, Assessment, Psychological Structure, Discipline